Multiple Antibiotic Resistance-Coliform Bacteria in Some Selected Fish Farms of the Central Region of Ghana - Cynthia Ayefoumi Adinortey; Denis Worlanyo Aheto; Alex Asomeni Boateng; Rosemary Agbeko (Scientifica)
This study aimed at assessing the quality of water and fishery products as well as the antibiotic resistance status of some selected fish farms of the Central Region of Ghana. Interview guides were administered to farmers to get data on farming practices and antibiotic use. Total coliform loads of catfish (Clarias gariepinus), tilapia (Oreochromis niloticus), and water samples were determined. Coliforms were identified through various biochemical assays, and their antibiotic resistance patterns were determined. Generally, the total coliform loads of water samples significantly surpassed those of fish samples p<0.05. The maximum and minimum antibiotic resistance percentages were recorded for ampicillin (96.83%) and gentamicin (6.35%), respectively. Although farmers stated that antibiotics were sparingly used, coliform bacteria isolated exhibited various antibiotic resistance patterns. Four out of six fish farms harboured some coliforms with multiple antibiotic resistance (MAR) indices above 0.2, an indication that these bacteria originated from potentially dangerous sources where antibiotics are regularly used.